Street sexual harassment as a barrier to the use of public space by women: the case of Panama - Araúz-Reyes, Nelva Marissa; Stanziola, Javier (Revista Colombiana de Ciencias Sociales, 2025)
The use of public space in urban areas reflects the degree to which democracy and other territorial rights can be exercised. However, the urban experience is not gender-neutral, as it is shaped by violence that primarily affects women through street sexual harassment. This study examines the impact of this form of harassment on women’s enjoyment of the right to public space in the metropolitan area of Panama City. The analysis begins by identifying perceived safety as the variable that explains the link between harassment and the use of public space. However, the results reveal how widespread this phenomenon is. Its prevalence contributes to its normalization, creating situations in which affected individuals do not immediately recognize this type of violence or its consequences. Although 9 out of 10 women reported having experienced street sexual harassment, they tend to resist it—either out of resignation in order to carry out their daily activities, or because they refuse to lose their right to enjoy public space.